GLOBALISASI DAN KEBIJAKAN PENDIDIKAN - Fahmi; Khasana, Alya Junisa; Agustin, Amanda; Ardinata, Prima Sena; Ayu, Wulan Rahma; Rappeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid technological advances, greater international interaction, and the flow of information are hallmarks of globalization, a process of cross-border integration that has a significant impact on the education sector. This study examines the concepts of globalization and education policy, the role of education policy in mitigating the impacts of globalization, the role of technology in education policy, and the challenges of its implementation. The methodology used is a qualitative descriptive approach that combines literature review methods from various relevant scientific sources. The findings of the discussion indicate that education policy plays a strategic role in ensuring equitable access to education, encouraging the use of technology, improving human resources, adapting the curriculum to 21st-century skills, and strengthening national character. Through increased access to knowledge and flexible digital learning, technology plays a crucial role in educational development. However, several obstacles remain in the implementation of education policy, including inadequate digital skills, inadequate infrastructure, and the potential loss of local cultural values. Therefore, to achieve a high-quality and globally competitive education system, inclusive, sustainable, and adaptive education policies are needed to combine local and global demands.